Runoff erosion and nutrient depletion in five Mediterranean soils of NE Spain under different land use. - Pardini, Giovanni; Gispert, Maria; Dunjó, Gemma (The Science of the total environment, 2003)
We investigated the influence of agricultural management and various plant covers related to the period of abandonment on soil properties, erosion and nutrient depletion in a typical Mediterranean area with sandy loam shallow soils. Cultivated soils (CS) with insufficient management, 5 year abandoned soils covered with meadow (A5), 25 year abandoned soils covered with dense scrubs (A25), 50 year abandoned soils covered with cork trees (A50) and soils in a 50 year pine reforested area (P50) were studied over a period of 6 months (May-October 1999). The soils were classified as Lithic Xerorthents. Both the differences in soil properties and response to rainfall events were mainly attributed to the different vegetation types and stages in land management. Principal components analysis (PCA) was performed on the results, by running the overall data determined after five rainfall events. The factors extracted by PCA of the samples by variables matrix represented the response of the environments to different rainfall intensities as a function of management or natural evolution after abandonment. CS environments showed the highest runoff and sediment yield as well as the highest amount of dissolved organic carbon (DOC) and nitrogen in runoff water. The sequence of abandonment (A5, A25 and A50) showed approximately the same runoff production, whereas eroded sediments (ES) and DOC were inversely correlated. Organic carbon in the ES and DOC in runoff water always increased with the period of abandonment, which accounted for consistent nutrient depletion. Nevertheless, the A50 environment (dominated by Quercus suber) showed the best soil properties, whilst the A25 environment with dense cover of Cistus monspeliensis and Calicotome espinosa seemed to cause a worsening effect on the soil's physical and chemical properties. This is probably because these environments are more severely damaged by wild fire occurrence. In terms of sediment yield, the P50 environment followed CS environment, indicating that reforestation followed by insufficient forest management may negatively affect both soil properties and response to the erosive action of rainfall.
Keywords: Abandonment; erosion; land management; nutrient availability; Nutrient losses; runoff; Sediment yield; soil properties; structure; Water retention

Runoff erosion and nutrient depletion in five Mediterranean soils of NE Spain under different land use. - Pardini, Giovanni; Gispert, Maria; Dunjó, Gemma (The Science of the total environment, 2003)
We investigated the influence of agricultural management and various plant covers related to the period of abandonment on soil properties, erosion and nutrient depletion in a typical Mediterranean area with sandy loam shallow soils. Cultivated soils (CS) with insufficient management, 5 year abandoned soils covered with meadow (A5), 25 year abandoned soils covered with dense scrubs (A25), 50 year abandoned soils covered with cork trees (A50) and soils in a 50 year pine reforested area (P50) were studied over a period of 6 months (May-October 1999). The soils were classified as Lithic Xerorthents. Both the differences in soil properties and response to rainfall events were mainly attributed to the different vegetation types and stages in land management. Principal components analysis (PCA) was performed on the results, by running the overall data determined after five rainfall events. The factors extracted by PCA of the samples by variables matrix represented the response of the environments to different rainfall intensities as a function of management or natural evolution after abandonment. CS environments showed the highest runoff and sediment yield as well as the highest amount of dissolved organic carbon (DOC) and nitrogen in runoff water. The sequence of abandonment (A5, A25 and A50) showed approximately the same runoff production, whereas eroded sediments (ES) and DOC were inversely correlated. Organic carbon in the ES and DOC in runoff water always increased with the period of abandonment, which accounted for consistent nutrient depletion. Nevertheless, the A50 environment (dominated by Quercus suber) showed the best soil properties, whilst the A25 environment with dense cover of Cistus monspeliensis and Calicotome espinosa seemed to cause a worsening effect on the soil's physical and chemical properties. This is probably because these environments are more severely damaged by wild fire occurrence. In terms of sediment yield, the P50 environment followed CS environment, indicating that reforestation followed by insufficient forest management may negatively affect both soil properties and response to the erosive action of rainfall.
The following values have no corresponding Zotero field: accession-num: 12798105
Keywords: Abandonment; erosion; land management; nutrient availability; Nutrient losses; runoff; Sediment yield; soil properties; structure; Water retention

Two vegetation maps of the same island: floristic units versus structural units - Lux, Andrea; Bemmerlein-Lux, Florian A (Applied Vegetation Science, 1998)
Abstract. This paper presents a comparison of two alternative methods to describe and map vegetation: on the basis of plant species and growth forms, respectively. A stratified random sampling was taken from spontaneous vegetation in 1989 on the volcanic island of Pantelleria (near Sicily, Italy). Cartographic and other comparisons of the results from classification and ordination analysis suggest that the major differences were associated with differences in the time scale of the underlying processes. Species results (leading to floristic vegetation units) were representative of longer-term processes, growth-form results (leading to structural vegetation units) with shorter-term processes. Further implications of these results are discussed.
Keywords: dynamics; fire; growth form; Italy; Pantelleria; structure; succession; Temporal scale

Restauración del bosque mediterráneo: aplicación de modelos de restauración a los encinares. - DE SIMÓN NAVARRETE, E; Investigaci, Nnavarrete Centro D E; Apartado, Agraria D E Granada (II Congreso Forestal Español, 1997)
The activities in order to restore the mediterraneam forests have been constitued by the restoration of the structures and natural vegetation communities in order to preserve the water and soil in the drainage basins. A restoration of the vegetation covers in a drainage basin with hydrological and biological criteria have been projected, using sorne reforestation works in order to the best utilitation of the water resources and the conservation of the soil. The Quercus rotundifolia is one of the most extended species in the mediterranean area and it is apply for the forestation of the lands. This paper proposes a model of applied for its restoration. K.W.:
Keywords: Evolution; hydrological process; mediterranean forest; Restoration; structure

Restauración del bosque mediterráneo: aplicación de modelos de restauración a los encinares. - DE SIMÓN NAVARRETE, E.; Investigaci, Nnavarrete Centro D. E.; Apartado, Agraria D. E. Granada (II Congreso Forestal Español, 1997)
The activities in order to restore the mediterraneam forests have been constitued by the restoration of the structures and natural vegetation communities in order to preserve the water and soil in the drainage basins. A restoration of the vegetation covers in a drainage basin with hydrological and biological criteria have been projected, using sorne reforestation works in order to the best utilitation of the water resources and the conservation of the soil. The Quercus rotundifolia is one of the most extended species in the mediterranean area and it is apply for the forestation of the lands. This paper proposes a model of applied for its restoration. K.W.:
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Evolution; hydrological process; mediterranean forest; Restoration; structure

Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H; Baptista, C (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)

Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H.; Baptista, C. (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)